The factors influencing whistleblowing among students in Universiti Mara Perlis / Fatin Syamimi Samsudin - Samsudin, Fatin Syamimi (2019)
This research aimed to determine the factors that influencing whistleblowing among students in Universiti Teknologi Mara (UiTM) Arau, Perlis. Whistleblowing is an important mechanism to reduce academic dishonesty in the institution. To gather the needed data, different references were used such as internet, books and newspapers. A distributed questionnaire with 320 of respondents, which includes students in full and part timer students. This study is to investigate whether independent variable (justification of dishonest behaviours, attitude justification of reporting and not reporting, subjective norms, perceived behaviour control and integrity culture) would affect the dependent variable (whistleblowing in academic dishonesty). The results revealed that justification of dishonest behaviours, attitude justification of reporting and not reporting, subjective norms, perceived behaviour control has positive significant with whistleblowing in academic dishonesty while integrity culture have negative significant with whistleblowing in academic dishonesty. The limitation of the study, significance of study and suggestions for future research also discussed.